2021
DOI: 10.31219/osf.io/2bq4u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dementia wellbeing and COVID-19: review and expert consensus on current research and knowledge gaps

Abstract: Objectives: In response to an NHS England enquiry, a UK-based working group, comprising dementia researchers from a range of fields and disciplines, aimed to describe the impact of the COVID-19 pandemic on dementia wellbeing and identify priorities for future research. Methods: We supplemented a rapid literature search (including unpublished, non-peer reviewed and ongoing studies/reports) on dementia wellbeing in the context of COVID-19 with expert group members’ consensus about future research needs. From thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 59 publications
1
29
1
Order By: Relevance
“…Staff perceived that a lack of access to their usual support networks and loneliness would be a significant challenge for older adults with mental illnesses or dementia. Indeed, a consensus group 16 identified the mental and physical impact of isolation as an important challenge for delivering the Preventing Well theme of the COVID‐19 Dementia Wellbeing Pathway 17 . Support provided by voluntary service organisations and well‐being packs produced for patients were seen as helpful innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Staff perceived that a lack of access to their usual support networks and loneliness would be a significant challenge for older adults with mental illnesses or dementia. Indeed, a consensus group 16 identified the mental and physical impact of isolation as an important challenge for delivering the Preventing Well theme of the COVID‐19 Dementia Wellbeing Pathway 17 . Support provided by voluntary service organisations and well‐being packs produced for patients were seen as helpful innovations.…”
Section: Discussionmentioning
confidence: 99%
“…These residents may find it difficult to understand, remember, and follow restrictions imposed on their movements in the context of isolation [3]. Further, the resulting disruption to their care routines and social interactions while in isolation negatively impacts their mental and physical health and quality of life [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, existing evidence based on carer reports and self-reports from PwD provided mixed results (Brown et al, 2020;Liu et al, 2021). On the one hand some studies (Boutoleau-Bretonniere et al, 2020;Canevelli et al, 2020;Lara et al, 2020;Rainero et al, 2020;Borelli et al, 2021) found that the pandemic accelerated decline in the cognitive, physical, functional, and mental health of PwD, as well as increased neuropsychiatric symptoms, behavioural problems, and loneliness among PwD (Barguilla et al, 2020;Boutoleau-Bretonniere et al, 2020;Canevelli et al, 2020;Cohen et al, 2020;Lara et al, 2020;Rainero et al, 2020;Vaitheswaran et al, 2020;Altieri and Santangelo, 2021;Azevedo et al, 2021;Borelli et al, 2021;Carlos et al, 2021;Liu et al, 2021;Tam et al, 2021;Tsapanou et al, 2021). On the other hand, some studies found that the pandemic had minimal negative impact or no impact on these outcomes (Canevelli et al, 2020;Cohen et al, 2020;Lara et al, 2020;Thyrian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%